LEGAL RISK MANAGEMENT IN THE AUSTRALIAN FITNESS INDUSTRY: IDENTIFYING THE PUBLIC LAW RISKS. (7th October 2012) - Keyzer, P
Abstract : Background: The fitness industry has a critical role to play in supporting healthy lifestyles. However exposure to legal liability risks represents a potentially significant cost to many service providers that may impact on business, and therefore service availability. Aims: There is a growing literature examining legal liability exposure in private law areas, such as personal injury, contracts and consumer law. However customers and employees of fitness services may also be subject to other psychosocial hazards such as sexual harassment, bullying, disability discrimination and discrimination on the ground of sexuality. Human rights law also creates important obligations to take into account. Methods: This paper reviews the literature on what are broadly termed 'pubic law' risks in the fitness industry. Outcomes: The paper identifies a number of research questions arising from this review for further research. Significance: This paper will help identify what sustainable changes could be made to Australian regulation for more effective risk management in the health and fitness industry in order to prevent the legal liability associated with the risk of adverse psycho-social health outcomes.